Changes in T2 Relaxation Times Associated with Maturation of the Human Intervertebral Disk - Krueger, E.C.; Perry, J.O.; Wu, Y.; Haughton, V.M. (American Journal of Neuroradiology, 2007)
BACKGROUND AND PURPOSE: By calculating T2 relaxation times for intervertebral disks, we tested the hypothesis that disk water concentration increases between the first and second decades of life.MATERIALS AND METHODS: In subjects younger than 10 years old (group 1) and subjects between 19 and 20 years old (group 2), a sagittal MR image of the lumbar spine was obtained with a modified 3D fast spin-echo (FSE) multi-echo sequence. T2 relaxation times for each voxel were calculated by fitting a logarithmic regression to the signal intensity in images at 16 different echo times. T2 times were averaged for each spinal disk in each group and differences tested for statistical significance by analysis of variance (ANOVA). T2 times along the vertical axis of the disk at the midline were plotted and inspected for evidence of a central lower signal intensity region (CLSIR) in the 2 groups. We tested the differences between groups for significance with the Student t test.RESULTS: Maps of T2 relaxation times showed different patterns in groups 1 and 2. The mean T2 relaxation times in each disk level in group 1 ranged from 74–95 ms and in group 2, from 91–119 ms. Differences between the 2 groups were significant (P < .001, ANOVA, P = .0002, Student t test of means); differences between levels were not. In group 2, development of a CLSIR was significantly more common than in group 1 (P = .0001, Student t test).CONCLUSIONS: T2 increases in the intervertebral disk between the first and second decades of life.